The impact of tax shields on bankruptcy risk and resource allocation - Olbert, Marcel (Review of Accounting Studies, 2025)
Abstract This paper investigates how tax loss carryforward (LCF) rules influence corporate bankruptcies and market-wide productivity. Analyzing data from 29 European countries, I find that stricter LCF deductibility limits significantly increase bankruptcy likelihoods. This is because stricter LCF deductibility limits lower the present value of net operating losses (NOLs) as tax assets, reducing the incentive to keep struggling firms alive. This effect is especially pronounced for business group firms, which can support struggling affiliates through internal capital markets to strategically exploit NOLs. My results suggest that lenient LCF deductibility limits can sustain unproductive firms, impacting market-wide resource allocation and productivity. These findings highlight the trade-off in tax policy between supporting firm survival and ensuring efficient resource allocation.